Endoscopic necrosectomy through a self-expandable metallic stent placed percutaneously for walled-off pancreatic necrosis - Yozo Sato; Kazuo Hara; Nozomi Okuno; Shinichi Murata; Takaaki Hasegawa; Hiroyuki Morinaga; Yuki Kimbara; Yugo Imai; Hidekazu Yamaura; Yoshitaka Inaba (International Journal of Gastrointestinal Intervention, 2020)
Walled-off pancreatic necrosis (WOPN) is defined as encapsulated necrotic tissue after severe acute pancreatitis. Treatment strategies for WOPN can be challenging. Although open surgical necrosectomy is the standard treatment for WOPN, it is associated with high rates of morbidity and mortality. Endoscopic necrosectomy, introduced recently, is a treatment option that produces lower rates of morbidity than does open surgery. We report a case of severe WOPN that could not be treated with the usual procedures. Although endoscopic necrosectomy of the left subphrenic and prepancreatic spaces was technically impossible, these spaces could be percutaneously drained. Finally, sufficient drainage of these spaces was achieved with endoscopic necrosectomy through the internal lumen of the self-expandable metallic stent placed percutaneously. This procedure was performed by an endoscopist and an interventional radiologist, and the multidisciplinary approach was useful.